Energy Engineering Analysis of Agricultural Product Drying Systems: A Review of Thermal Efficiency and Energy Consumption - Arjal Tando (Fakultas Teknologi Pertanian Unsultra, 2025)
Drying is a crucial post-harvest process in agricultural product handling, aimed at reducing moisture content to a safe equilibrium level against microbial and enzymatic activity. Energy and thermal efficiency have become major issues in the development of modern drying systems oriented toward sustainability. This study aims to review various energy engineering approaches applied to agricultural drying systems, focusing on improving thermal efficiency and reducing energy consumption. Based on recent literature, renewable energy–based dryers such as solar dryers, solar–biomass hybrid systems, and heat pump technologies have demonstrated significant improvements in energy efficiency. The integration of digital technologies, including the Internet of Things (IoT) and artificial intelligence (AI), also contributes to drying optimization through adaptive control systems. The review reveals that conventional dryers typically exhibit thermal efficiencies below 20%, whereas modern engineered systems can achieve 45–70%, depending on design and applied technology. Therefore, energy engineering innovations have great potential to enhance the efficiency and sustainability of agricultural drying systems while supporting national food security and energy efficiency goals.